Oxygen saturation targets for adults with acute hypoxemia in low and lower-middle income countries: a scoping review with analysis of contextual factors - Herbst, Austin; Goel, Swati; Beane, Abi; Brotherton, B. Jason; Dula, Dingase; Ely, E. Wesley; Gordon, Stephen B.; Haniffa, Rashan; Hedt-Gauthier, Bethany; Limbani, Felix; Lipnick, Michael S.; Lyon, Samuel; et al. (Frontiers in Medicine, 2023)
Knowing the target oxygen saturation (SpO2) range that results in the best outcomes for acutely hypoxemic adults is important for clinical care, training, and research in low-income and lower-middle income countries (collectively LMICs). The evidence we have for SpO2 targets emanates from high-income countries (HICs), and therefore may miss important contextual factors for LMIC settings. Furthermore, the evidence from HICs is mixed, amplifying the importance of specific circumstances. For this literature review and analysis, we considered SpO2 targets used in previous trials, international and national society guidelines, and direct trial evidence comparing outcomes using different SpO2 ranges (all from HICs). We also considered contextual factors, including emerging data on pulse oximetry performance in different skin pigmentation ranges, the risk of depleting oxygen resources in LMIC settings, the lack of access to arterial blood gases that necessitates consideration of the subpopulation of hypoxemic patients who are also hypercapnic, and the impact of altitude on median SpO2 values. This process of integrating prior study protocols, society guidelines, available evidence, and contextual factors is potentially useful for the development of other clinical guidelines for LMIC settings. We suggest that a goal SpO2 range of 90-94% is reasonable, using high-performing pulse oximeters. Answering context-specific research questions, such as an optimal SpO2 target range in LMIC contexts, is critical for advancing equity in clinical outcomes globally.